THE IMPACT OF DRILL PRACTICE ON VOCABULARY ACQUISITION IN YOUNG ENGLISH LEARNERS - Siti Nuraeni (National Conference on Language, Education, and Technology Proceeding, 2023)
Language acquisition is a multifaceted process, particularly for young learners embarking on the journey of acquiring a second language. Central to this acquisition is the development of vocabulary, a fundamental component pivotal for effective communication and comprehension skills. Amid the myriad of pedagogical strategies employed for vocabulary instruction, the drill practice method has garnered attention due to its structured and repetitive nature. This study endeavors to scrutinize the impact of drill practice on vocabulary acquisition among young English learners, focusing on aspects such as short-term retention, long-term recall, engagement, and transferability to real-world language usage. By employing a mixed-methods research design, encompassing both quantitative and qualitative approaches, this investigation delves into the efficacy of the drill practice approach in enhancing vocabulary learning outcomes. The quantitative facet of this study involves a pre-test and post-test experimental design, providing a statistical evaluation of the effects of drill practice intervention. Notably, the mean pre-test score indicates participants' initial grasp of the targeted vocabulary, while the post-test mean score reflects a discernible improvement, signifying a positive shift in vocabulary acquisition. The ensuing paired t-test corroborates the significance of this advancement, thereby accentuating the efficacy of the drill practice intervention. Additionally, the calculated Cohen's d effect size highlights the practical significance of the intervention's impact on vocabulary acquisition.